2023
DOI: 10.3390/plants12122249
|View full text |Cite
|
Sign up to set email alerts
|

Hormetic Effect of Glyphosate on the Morphology, Physiology and Metabolism of Coffee Plants

Abstract: Glyphosate is a nonselective herbicide of systemic action that inhibits the enzyme 5-enolpyruvylshikimate-3-phosphate synthase, thus compromising amino acid production and consequently the growth and development of susceptible plants. The objective of this study was to evaluate the hormetic effect of glyphosate on the morphology, physiology, and biochemistry of coffee plants. Coffee seedlings (Coffea arabica cv Catuaí Vermelho IAC-144) were transplanted into pots filled with a mixture of soil and substrate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…This explains the effects we observed when exposing T. ciliata plants to doses of 9.6 and 19.2 g ha −1 of glyphosate, which induced a better photochemical performance index and less energy dissipation in the form of heat, which indicates a reduction in stress caused by the incidence luminous. Similarly, Costa et al [ 66 ] showed that glyphosate applied between doses of 4.4 to 55 g ha −1 in Coffea arabica plants improves the photochemical efficiency of PSII.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This explains the effects we observed when exposing T. ciliata plants to doses of 9.6 and 19.2 g ha −1 of glyphosate, which induced a better photochemical performance index and less energy dissipation in the form of heat, which indicates a reduction in stress caused by the incidence luminous. Similarly, Costa et al [ 66 ] showed that glyphosate applied between doses of 4.4 to 55 g ha −1 in Coffea arabica plants improves the photochemical efficiency of PSII.…”
Section: Discussionmentioning
confidence: 94%
“…The reduction in A in plants grown under a sublethal dose of 76.8 g ha −1 resulted in lower rates of production or transport of assimilated photosynthates and, consequently, reduced height. According to Costa et al [ 66 ], these alterations are responsible for growth decline. However, a dose of 76.4 g ha −1 induced stem thickening, similar to the dose used by Marques et al [ 68 ], who applied 60 g ha −1 to Cedrela odorata , a species of the same family (Meliaceae), also known as cedar.…”
Section: Discussionmentioning
confidence: 99%
“…19 In addition to herbicidal applications, low doses of glyphosate that stimulate plant growth have become a considerable research topic. [20][21][22][23][24] Low glyphosate doses can increase photosynthetic pigments content and stimulate photosynthesis, 25,26 yet the specific mechanisms, especially the function of PSII in hormesis, remain unclear. 15,27 In this study, we mainly focus on the biphasic relationship between glyphosate dose and tomato (Solanum lycopersicum L.) plant growth, and aim to evaluate the potential of hormesis to enhance plant tolerance against stress caused by diuron (DCMU), a presentative photosynthesis inhibitor.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to herbicidal applications, low doses of glyphosate that stimulate plant growth have become a considerable research topic 20–24 . Low glyphosate doses can increase photosynthetic pigments content and stimulate photosynthesis, 25,26 yet the specific mechanisms, especially the function of PSII in hormesis, remain unclear 15,27 …”
Section: Introductionmentioning
confidence: 99%